2018
DOI: 10.15835/nbha47111248
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcoding in Selected Species and Subspecies of Rye (Secale) Using Three Chloroplast Loci (matK, rbcL, trnH-psbA)

Abstract: DNA barcoding is a relatively new method of identifying plant species using short sequences of chloroplast DNA. Although there is a large number of studies using barcoding on various plant species, there are no such studies in the genus Secale. In this study the plant material consisted of 10 cultivated and non-cultivated species and subspecies of rye genus. Three chloroplast DNA regions (rbcL, matK, trnH-psbA) were tested for their suitability as DNA barcoding regions. Universal primers were used, and sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
(64 reference statements)
1
4
0
Order By: Relevance
“…Our results showed that the partial region of the matK gene amplified and sequenced gave high polymorphism between all studied species (58.37%). This nearly agreed with Skuza et al (2019) who observed that nucleotide sequences had a high variability within matK and rbcL regions. Polymorphism of the sequences was 2.2% in the rbcL region, while in the matK region was 6.5%.…”
Section: Discussionsupporting
confidence: 91%
“…Our results showed that the partial region of the matK gene amplified and sequenced gave high polymorphism between all studied species (58.37%). This nearly agreed with Skuza et al (2019) who observed that nucleotide sequences had a high variability within matK and rbcL regions. Polymorphism of the sequences was 2.2% in the rbcL region, while in the matK region was 6.5%.…”
Section: Discussionsupporting
confidence: 91%
“…This causes a significantly reduction of progress in rye breeding that can be enriched with functional traits derived from wild rye species. In the genus, the wild species Secale sylvestre Host ( 1809) is singularized by several genetic peculiarities (Bennett and Smith 1976;Singh and Röbbelen 1977;Shang et al 2006;Zhou et al 2010;Skuza et al 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…These markers are highly informative for identifying and differentiating plant species. Recently, the use of DNA barcoding based on the markers rbcl, ITS, and MatK has gained significant traction in the field of plant species authentication . In this study, all three markers were used for the identification of E.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the use of DNA barcoding based on the markers rbcl, ITS, and MatK has gained significant traction in the field of plant species authentication. 36 In this study, all three markers were used for the identification of E. tithymaloides . The sequence match with rbcl loci showed a match of 98.64 to 99.83% with the top five hits from the BLAST analysis.…”
Section: Discussionmentioning
confidence: 99%